c)(xsupra2y)^4 *(y²suprax²)^4=
e)(-1supra2x)^5 * (-2xsupray)^5=
f)(3msupra4n)^4 * (2nsupra9m)^4=
^ inseamna la puterea
Răspunsuri la întrebare
Răspuns de
1
c)(x/2y)⁴ *(y²/x²)⁴=
=x⁴/16y⁴ *(y⁸/x⁸)=
=y⁴/16x⁴
e)(-1/2x)⁵ * (-2x/y)⁵=
=-1/32x⁵ * -32x⁵/y⁵=
=-1/ y⁵
f)(3m/4n)⁴ * (2n/9m)⁴=
=3⁴m⁴/4⁴n⁴ * 16n⁴/9⁴m⁴=
=9²m⁴/4⁴n⁴ * 4²n⁴/9⁴m⁴=
=1/4² * 9²=
=1/1296
=x⁴/16y⁴ *(y⁸/x⁸)=
=y⁴/16x⁴
e)(-1/2x)⁵ * (-2x/y)⁵=
=-1/32x⁵ * -32x⁵/y⁵=
=-1/ y⁵
f)(3m/4n)⁴ * (2n/9m)⁴=
=3⁴m⁴/4⁴n⁴ * 16n⁴/9⁴m⁴=
=9²m⁴/4⁴n⁴ * 4²n⁴/9⁴m⁴=
=1/4² * 9²=
=1/1296
ionutdiaconu371:
va multumesc frumos
Alte întrebări interesante
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Biologie,
10 ani în urmă
Studii sociale,
10 ani în urmă